2017
DOI: 10.1177/2192568217716144
|View full text |Cite
|
Sign up to set email alerts
|

Complications Associated With Spine Surgery in Patients Aged 80 Years or Older: Japan Association of Spine Surgeons with Ambition (JASA) Multicenter Study

Abstract: Study Design:Retrospective study of registry data.Objectives:Aging of society and recent advances in surgical techniques and general anesthesia have increased the demand for spinal surgery in elderly patients. Many complications have been described in elderly patients, but a multicenter study of perioperative complications in spinal surgery in patients aged 80 years or older has not been reported. Therefore, the goal of the study was to analyze complications associated with spine surgery in patients aged 80 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 27 publications
5
46
0
Order By: Relevance
“…However, in the elderly, another major concern is the anesthesia effect on unrecognized dementia and cognitive decreases besides what occurs in the more obvious patients with a diagnosis of Alzheimer's disease [16][17]. In a study of osteoporotic hip fractures, in an aged population, similar to our patients, with osteoporotic vertebral fractures and stenosis, 19.2% under further detailed medical history was found to have dementia and 41.8% some degree of a cognitive disorder [27].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…However, in the elderly, another major concern is the anesthesia effect on unrecognized dementia and cognitive decreases besides what occurs in the more obvious patients with a diagnosis of Alzheimer's disease [16][17]. In a study of osteoporotic hip fractures, in an aged population, similar to our patients, with osteoporotic vertebral fractures and stenosis, 19.2% under further detailed medical history was found to have dementia and 41.8% some degree of a cognitive disorder [27].…”
Section: Discussionsupporting
confidence: 58%
“…There is also another group of elderly patients who either do not want extensive open surgery or are at higher risk and may be more suitable for more minimally invasive procedures with the caveat that if symptoms do not sufficiently improve there is the option to still proceed with more extensive surgery [18]. Balancing all these factors, patients in the 80s and 90s can still undergo different levels of extensive lumbar decompression and fusion with no significantly greater peri-operative risk and acceptable outcomes [19][20]. Over the last 10 or more years, minimally invasive spinal procedures have evolved, which combined with the use of local anesthesia enable surgery to be performed as an outpatient and allowing quicker reduction of pain and return to full activity.…”
Section: Introductionmentioning
confidence: 99%
“…10 Consistent with this, there is an increasing number of patients aged 80 years and older who are being considered for, or undergoing, elective or emergency surgery. [11][12][13][14] Although many studies have associated this with increased rates of morbidity and mortality, 15,16 others have demonstrated low complication rates with appropriate patient selection. 17 Therefore, it is timely to validate an accurate tool to assist with preoperative risk stratification in patients 80 years and older who are being considered for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…18,26 Kobayashi et al conducted a multicenter retrospective study of 262 spine surgeries performed in patients 80 years of age or older and identified a high complication rate (29%). 16 Nasser and colleagues found a higher complication rate associated with spine surgery in prospective studies than in retrospective studies. 22 To the best of our knowledge, a multicenter prospective all-case investigation of perioperative complications of spine surgery in patients 80 years of age or older has not previously been conducted, and the results of our current study are potentially able to determine the perioperative complications of spine surgery.…”
Section: Discussionmentioning
confidence: 98%
“…The rate of perioperative complications in spine surgery has been reported to range from 5.6% to 35% in patients 80 years of age or older. 12,16,18,19,21,24,26,28,34 The majority of earlier studies on perioperative complications were retrospective. One systematic review showed that the incidence of complications was higher in prospective studies than in retrospective studies (19.9% vs 16.1%).…”
mentioning
confidence: 99%